The Impact of Restaurant Tax Contribution on Regional Tax and Strategies to Achieve Restaurant Tax Targets in Bekasi City (Case Study at the Regional Revenue Agency of Bekasi City) - Rosma Titis Hapsari; Adler Haymans Manurung; Wastam Wahyu Hidayat; Idel Eprianto; M. Jhonni Sinaga (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the contribution of restaurant taxes to regional tax revenue and strategies to achieve restaurant tax targets in Bekasi City, referencing Law No. 1 of 2022 on Financial Relations Between the Central and Regional Governments. The research emphasizes increasing Local Own-Source Revenue (PAD) through regional taxes, specifically restaurant taxes. Using a quantitative approach with multiple regression analysis, the study evaluates the impact of external and internal variables such as tax extensification, tax collection, and technological innovation on restaurant tax revenue. The findings indicate that technological innovation and tax collection significantly influence regional tax revenue, with a coefficient of determination (R²) of 92.18%. While tax extensification does not show a significant individual effect, collectively, these variables explain most of the variation in regional tax revenue. The study identifies gaps in understanding the factors affecting restaurant tax target achievement and the need for more effective tax management strategies. Recommendations for local governments include enhancing technology use in tax administration and strengthening the tax collection system to improve taxpayer compliance. This research contributes to the development of more effective and efficient tax policies to support local economic growth in Bekasi City.